INFLUÊNCIA DO TREINAMENTO CURTO DE ALTA INTENSIDADE NOS ESCORES DE DEPRESSÃO E APTIDÃO FÍSICA DE PESSOAS COM DEPRESSÃO: ENSAIO CLÍNICO RANDOMIZADO - Jessica Alves Ribeiro (2022)
Depression is a major public health problem associated with morbidity and mortality; moreover, people with depression have sedentary behaviors and low levels of physical fitness and the main reason used to explain this behavior is the lack of time and pleasure. For this reason, the short sprint interval training (sSIT) protocol may be an alternative due to its low volume and probably good adherence. Objective. The aim of the present study is to analyze the effects of sSIT on depression scores and physical fitness in women diagnosed with depression. Materials and methods. This study evaluated 17 women, with a mean age of 41.7±7.8 years, sedentary, with moderate and severe depression who were randomly allocated into two groups: control and experimental. The sSIT training protocol consisted of performing, over 6 sessions in two weeks, 4-12 sprints of 5 s, with an active rest interval of ≥30 s at 50 W, with a 48-hour rest between sessions, with linear periodization. and an individualized selection of the number of sprints in each session. The control group remained using their medications and routine of daily tasks, without engaging in physical exercise for two weeks. All the patients fulfilled the International Neuropsychiatric Interview (MINI) for the diagnosis of depressive disorder and were assessment for calculation of depression scores by using the 21-item Hamilton Scale, and answered the International Physical Activity Questionnaire (IPAQ) and the Physical Activity Readiness Questionnaire (PAR-Q). In the first and fourth weeks, they were submitted to an assessment of body composition, handgrip strength, muscle power of the lower limbs with the countermovement jump, maximal incremental test on a cycle ergometer, and the number of steps over 4 days a week and one at the weekend. Results. Patients of the experimental sSIT group exhibited an improvement of aerobic power and capacity (140±15 vs. 155±15 W, p=0.016; 569±75 vs. 653±100 s, p<0.001) and a greater number of daily steps (13625±11309 vs. 16643±15371., p=0.009) from the 1st to the 4th week, after the training period. In addition, they showed a lower depression scores, which changed from 22.5±7 in the 1st week to 24±8 in the 4th week (p<0.001). However, the sSIT group did not change body mass, BMI, and waist and abdominal circumferences. However, the % of fat decreased significantly (p<0.001). Conclusion. The sSIT protocol appears to be an efficient training protocol to be considered in people with depression. Future randomized clinical trials with larger samples should confirm these promising results. Keywords: Depression; Short high-intensity training; Physical aptitude.